Impact of Workplace Alienation on Managers and Engineers (Indian Journal of Management and Language (IJML), 2025)
Workplace alienation is described as a state of being in which the employee is demotivated and disinterested in their individualized role and responsibilities at their place of work. The psychological feeling of alienation or separation from their employer and colleagues, and having very little or no passion at all towards their work. This kind of occupational scenario is observed as an implication of certain employer-based actions toward the employee. These actions may comprise being unable to recognize the drive and successes, criticizing the output and the employee, lack of empathy towards the employee, and other issues. This study focuses on understanding the Work Alienation (WA) of Engineers and Managers; and also analyses the influence of sociodemographic features on the OSE among the employee groups. The study was conducted in a major manufacturing Public Sector Unit, located in Mysore. The stratified random sample consisted of up to a hundred and twenty samples selected as per inclusion and exclusion criteria. The data was collected using the WA tool, along with a demographic data sheet. The data was analyzed using statistical tools like Regression analysis, Two-way ANOVA, and Duncan’s Multiple Range Test (DMRT). The results of the study are Engineers and Managers did not differ significantly in their WA scores; the interaction effect between occupation type and different income, age, and years of work experience, are nonsignificant which shows that WA is similar in employees irrespective of the occupation they have. To conclude, WA influences employees' beliefs in their competencies in being able to control their work, thereby over such scenarios that impact them. Beliefs about one’s efficacy influence choices in life, motivation levels, functioning levels, resilient behaviour towards adverse situations, and being vulnerable to stress and its lifethreatening consequences.